Pemanfaatan Gulma Siam (Chromolaena odarata L.) Sebagai Adsorben Logam Timbal - Erni Mohamad; Intan J. Oputu; Julhim S. Tangio (Jambura Journal of Chemistry, 2020)
This study aims to utilize (Chromolaena odorata L) as a metal adsorbent. The methods used to make activated charcoal are dehydration, carbonization, and activation. The activated carbon is then characterized to obtain activated charcoal that can be applied, then optimized. The results of activated carbon characterization obtained have reached the activated carbon quality requirements based on the Indonesian Industry Standard (SII No. 0258-88). Based on the adsorption test, the optimum pH of Pb2+ (Pb (NO3) 2 (in distilled water) Chromolaena odorata L charcoal activated by NaOH 0.2 M under varying pH (2,3,4,5,6) is at pH 5 with 69.00% absorption. The optimum contact time required for Pb ion adsorption is 4 hours at variation (1-5 hours) with 70.19% absorption. The optimum concentration at variation (concentration 20; 40; 60; 80; 100 ppm) on Pb ion adsorption is 100 ppm with 76.15% absorption. The optimum heating time is a variation of 1.5; 2; 2.5; and 3 hours of Pb ion adsorption is one hour 30 minutes with an absorption of 65.95%. Based on the optimization results, the activated carbon from the Chromolaena odorata L can be used as an adsorption material against the contamination of lead heavy metals (Pb).